2018
DOI: 10.1108/jwl-03-2017-0028
|View full text |Cite
|
Sign up to set email alerts
|

Understanding informal learning in small- and medium-sized enterprises in South Korea

Abstract: Purpose This paper aims to explore informal learning experiences among employees working in South Korean small- and medium-sized enterprises (SMEs) with fewer than 100 employees. This study specifically seeks to understand the characteristics of informal learning in Korean SMEs and culturally sensitive contextual factors that shape informal learning. Design/methodology/approach To understand the complex, holistic nature of the phenomenon, the current study used a phenomenological qualitative approach. Eighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…Marsick (2009) pointed out that the impact of national culture on informal learning is still unknown and called for more research. For example, Jeong, McLean, and Park (2018), in their qualitative study, found that Korean culture (e.g., Confucianism, face-saving) makes a profound impact on shaping experience of informal learning among employees working in SMEs. Bednall et al (2014) also recommended, that researchers investigate the potential moderating effects of national culture on the association between performance appraisal and informal learning.…”
Section: Implications For Hrd Researchmentioning
confidence: 99%
“…Marsick (2009) pointed out that the impact of national culture on informal learning is still unknown and called for more research. For example, Jeong, McLean, and Park (2018), in their qualitative study, found that Korean culture (e.g., Confucianism, face-saving) makes a profound impact on shaping experience of informal learning among employees working in SMEs. Bednall et al (2014) also recommended, that researchers investigate the potential moderating effects of national culture on the association between performance appraisal and informal learning.…”
Section: Implications For Hrd Researchmentioning
confidence: 99%
“…SMBs cannot invest as much time and financial resources in formal personnel development as larger enterprises (Abel and Wagner 2017;Coetzer et al 2017;Decius and Schaper 2017). Furthermore, learning in SMBs is characterized by the sudden need for workers to learn and to apply what they have learned directly (Jeong et al 2018b). In such cases, it is challenging for SMBs to release employees to participate in (external) formal trainings, as it is more difficult for SMBs than for larger companies to compensate for the temporary absence of staff in often strictly planned work processes (Blings 2008).…”
mentioning
confidence: 99%
“…Specifically in Korea, the highest power distance culture in the world (Hofstede, 2018), clear unequal relationships between people who have different power are common throughout society (Chai et al, 2016). The cultural behavior of power inequality is typically called sang-myung-ha-bok , which describes unconditional obedience to superiors (Rowley & Bae, 2004), or gab-eul , which clearly distinguishes and underlines the power difference between people in which gab (people with strong power) rule over eul (people with weaker power; Jeong, McLean, & Park, 2018). Gender, in Korea, is a major factor associated with power in the workplace and is linked to position and authority.…”
Section: National Culture and Women’s Leadershipmentioning
confidence: 99%